The Effects of a Sodium Carbonate Catalyst on Calorific Value, Flash Point, Cetane Index, and pH of Tire Pyrolysis Oil - Job Bosire Omwoyo; William Mengo (International Journal of Chemical Engineering)
The large volume of tire waste generated globally poses a major waste disposal problem. In the natural environment, disposed of tires do not degrade easily, but they can be processed through pyrolysis, to get char, gas, and oil. In this study, tire pyrolysis was done using 0.00%, 1.50%, 2.50%, 5.00%, 7.50%, and 10.00% sodium carbonate catalyst in the feed material to produce oil. An evaluation of the effects of the catalyst on the cetane index, calorific value, pH level, and flash point of tire pyrolytic oil (TPO) was carried out since these are the essential properties in relation to safety in its handling and efficiency in engine performance and operation. There was a decrease in the calorific value by 3.09%, the flash point by 37.25%, and the cetane index by 71.2% with increasing catalyst percentage, while the pH was found to increase by 19.78% (between 0.00 and 5.00% sodium carbonate catalysts) and then decreased when more than 5.00% of the catalyst was employed. These results will provide theoretical information that will guide its handling and usage as fuel.